Environmental contamination associated with some abandoned mines in Central Portugal - Antunes, I.M.H.R. (2011)
At Segura, aplite-pegmatite veins with casserite and lepidolite, Sn-W, and Ba-Pb-Zn quartz veins were exploited; mine tailings were left exposed. Sn, W, B, As, and Cu anomalies in stream sediments and soils are related to the Sn-W quartz veins, while Ba, Pb and Zn anomalies are associated with the Ba-Pb-Zn veins. Soils are contaminated in Sn, B, As, and Ba and must not be used for agriculture and human residences or industry. The waters are contaminated in As, Fe and Mn and should not be used for human and agricultural activities. Sn, B, Cu, and Pb were not detected in waters.